The Presidents in American history - Beard, Charles Austin 1874-1948.; Beard, William 1907-. (New York J. Messner, 1953)
Briefly summarizes the achievements of each presidential administration from Washington to Nixon. Includes a biographical digest giving basic facts about each President, a list of Vice-Presidents and cabinet members, and the results of each presidential election.
Keywords: Presidents -- Juvenile literature. -- United States -- Biography; Presidents